Chemotherapy is a risk factor of lymphopenia before adjuvant radiotherapy in breast cancer - Fang Chen; Lingyu Ma; Qian Wang; Manling Zhou; Yaqing Nong; Haiman Jing; Ying Han; Yaya Liu; Yulin Hu; Hao Yu; Pingfu Fu; Feng‐Ming ( Spring) Kong (Cancer Reports, 2022)
Abstract Background Lymphopenia can decrease immune function of the host and is a known risk factor for poor prognosis in malignant tumors. Radiation induced lymphopenia was common in patients with breast cancer and was also reported to have a negative effect on long‐term outcome. Aims Lymphopenia may be associated with baseline immune status before radiotherapy (RT). This study aimed to explore the rate and risk factors of lymphopenia before start of the adjuvant RT in patients with breast cancer. Methods Patients with invasive breast cancer treated from March 2015 to February 2020 and with peripheral lymphocyte counts (PLC) available within 7 days from the beginning of RT were eligible for this study. Data were presented as mean and 95% confidence interval unless otherwise specified. The risk factors of low PLC before RT were identified using univariate and multivariable linear regressions. Results A total of 1012 consecutive patients met the study criteria. The mean PLC before RT commencement was 1.58*109/L (95%CI: 1.55–1.62*109/L) with 15.2% (95%CI: 13.1%–17.6%) CTCAE defined lymphopenia, rendering 12.3%, 2.6%, 0.3%, and 0% for grade 1, 2, 3 and 4 respectively. Univariate and multivariable linear regression showed prior chemotherapy was the most significant risk factor (p < .001) for low PLC, while age, menopausal status and lymph node stage were not (all ps > .05). A total of 912 (90.1%, 95%CI: 88.1%–91.9%) patients had chemotherapy before adjuvant RT in this study. In patients with HR+/HER2‐ breast cancer, 69.0% (95%CI: 63.0%–74.5%) N0 and 98.1% (95%CI: 95.1%–99.5%) N1 had also received chemotherapy. Conclusions Patients with breast cancer might have lymphopenia from prior chemotherapy at the start of adjuvant RT which could have negative effect on long‐term outcome. It is also noted that most of the patients with HR+/HER2‐, early‐stage breast cancer were treated with aggressive chemotherapy without knowing the risk of chemotherapy induced lymphopenia. Future study on predictive or prognostic multigene assays is warranted to avoid unnecessary chemotherapy and subsequent lymphopenia in patients with low risk breast cancer.